1993
DOI: 10.1159/000201036
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of Inflammatory Bowel Disease in Bologna, Italy – Incidence and Risk Factors

Abstract: Recently, in Bologna, an inflammatory bowel disease incidence of 7.7/105/year has been calculated, about one third of that reported in Northern Europe, confirming the existence of a ‘North-South gradient’. A first peak of incidence was observed at 20-29 years of age and a second peak at 60-69 years of age for ulcerative colitis (UC) alone. A prevalence of UC males, mainly after the 7th decade, and of Crohn’s disease (CD) females in the first peak was found. A greater frequency of ex-smokers in UC, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 7 publications
0
14
1
5
Order By: Relevance
“…In fact, the EC‐IBD showed that the lowest incidence of CD in Europe was in Ioannina in northwest Greece (0.9, 95% CI, 0.0–2.2) 7. A north–south gradient in IBD incidence has been found in Europe and the United States but recent studies have shown that this gradient is narrower than previously believed 17, 19…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, the EC‐IBD showed that the lowest incidence of CD in Europe was in Ioannina in northwest Greece (0.9, 95% CI, 0.0–2.2) 7. A north–south gradient in IBD incidence has been found in Europe and the United States but recent studies have shown that this gradient is narrower than previously believed 17, 19…”
Section: Discussionmentioning
confidence: 96%
“…The highest incidence rates and prevalence for both CD and UC have been reported from northern Europe, the United Kingdom, and North America 11–15. The lowest figures are found in southern countries; however, few studies on the incidence of IBD have been carried out in southern Europe 16, 17. The multicenter European Collaborative Study on Inflammatory Bowel Disease (EC‐IBD) reported blended incidence rates between 8.7 and 11.8 cases per 100,000 person years for UC and between 3.9 and 7.0 cases per 100,000 person‐years for CD 7…”
Section: Discussionmentioning
confidence: 99%
“…Studies from southern Europe have previously reported incidence values far lower than the above mentioned [Maté-Jimenez et al 1994;Tsianos et al 1994;Martinez-Salmeron et al 1993;Tragnone et al 1993;Trallori et al 1991;Vucelic et al 1991]. However, these studies were retrospective in design and thereby subject to different sources of bias.…”
Section: Occurrencementioning
confidence: 95%
“…In case-control studies, which have reported the dietary intake prior to the diagnosis of ulcerative colitis, the results have been conflicting with several not showing any affect on risk [2,3,4,5,6] and others reporting either an increased [7,8,9,10,11,12,13,14,15] or decreased risk [10,11,12,13, 15, 16]. An increased risk has been reported for carbohydrate and starch [7], cereal products [10], sugar [17], fat [10, 12, 13], cholesterol [12], protein [7], monounsaturated and polyunsaturated fatty acids [9, 12], fast foods [11], cola drinks [14], chocolate [14] and sweets [15]. A decreased risk was reported for fruit and vegetable fibre [10, 16], vitamin C [12,][15] vitamin E [13] and coffee [11, 15].…”
Section: Introductionmentioning
confidence: 99%